The Ophryotrocha labronica group (Annelida: Dorvilleidae)— with the description of seven new species - Paxton, Hannelore; Åkesson, Bertil (Zootaxa, 2010)
This paper reviews the group of gonochoristic Ophryotrocha species, known as the “O. labronica group”. This informal group is chararacterised by its unique maxillary P- and K-forceps and dorsomedian rosette glands. All members of the group are primarily gonochoristic and almost all have the diploid complement of chromosomes of 2n = 6. External morphological differences within the group are very slight. In males and females of all species the P-type maxillae change at maturity to the K-type with the right forceps being bifid. A jaw fossil from the Upper Cretaceous, attributable to the O. labronica group, attests to the long history of the group. As herein defined, the group includes: O. labronica labronica, O. labronica pacifica, O. costlowi sp. nov., O. dimorphica, O. japonica sp. nov., O. macrovifera sp. nov., O. notoglandulata, O. permanae sp. nov., O. robusta sp. nov., O. rubra sp. nov., O. schubravyi, O. vellae sp. nov., O. olympica, nom. nud., O. prolifica, nom. nud., and O. sativa, nom. nud.. Seven species are formally described and diagnoses are provided for all remaining taxa in the taxonomic section. This is followed by an illustrated discussion of the morphology, reproductive traits, and relationships of the members of the informal group.